2022
DOI: 10.3389/fcimb.2022.938477
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypicand Genotypic Characterization of Clinical Isolates of Intracellular Adherent–Invasive Escherichia coli Among Different Stages, Family History, and Treated Colorectal Cancer Patients in Iran

Abstract: There is increasing evidence showing that microbial dysbiosis impacts the health and cancer risk of the host. An association between adherent–invasive Escherichia coli (AIEC) and colorectal cancer (CRC) has been revealed. Cyclomodulins (CMs) have been receiving increasing attention for carcinogenic changes. In this study, the incidence and features of intracellular AIEC and cyclomodulin-encoding genes were investigated and the phylogenetic grouping and genetic relatedness were evaluated. E. coli strains were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…A recent worldwide assessment of cancer triggers attributed to infection and other risk factors highlights the necessity of controlling cancers based on the local pattern profile of risk factors 3) . The prevalence of viral infection in malignant tissue samples of GIT varies considerably in different studies, and this inconsistency seems to be mainly related to technical aspects 17,18) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent worldwide assessment of cancer triggers attributed to infection and other risk factors highlights the necessity of controlling cancers based on the local pattern profile of risk factors 3) . The prevalence of viral infection in malignant tissue samples of GIT varies considerably in different studies, and this inconsistency seems to be mainly related to technical aspects 17,18) .…”
Section: Discussionmentioning
confidence: 99%
“…Esophageal cancer (EC) with a different geographical distribution ranks as the seventh most common cancer and the sixth, in terms of mortality. Although several risk factors, including host genetics, gut microbiome, and environmental factors, may affect a person's vulnerability to the development of cancers of the digestive tract 3) , the continuous active inflammatory response caused by various viral infections may increase the risk of different malig-nancies. The involvement of causative pathogens, such as viruses in GIT cancers has been reported in different studies 4) .…”
Section: Introductionmentioning
confidence: 99%
“…The invasion level defined as the percentage of intracellular bacteria compared to the initial inoculum, was then measured. An isolate was considered invasive if its invasion level was ≥ 0.1% [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…From our previous study, a collection of 74 intracellular E. coli strains was isolated from specimens of colorectal biopsies of 150 participants including patients with CRC [CRC1, carcinoma in situ (Tis); CRC2, tumor stage (T1-T2 or T3); CRChis, patients who had a history of CRC that were referred for a 6-month follow-up; FH, individuals who have a family history of CRC, and the healthy control group]. Adhesion and Invasion Assay and Intramacrophage Cell Survival Test were carried out as previously described, and 24 strains were identified as AIEC pathotypes ( Kamali Dolatabadi et al, 2022 ). The study was approved by the Ethics Committee of Isfahan University of Medical Sciences (approval no.…”
Section: Methodsmentioning
confidence: 99%
“…The composition of microorganisms in the gut ecosystem is among the environmental factors that may contribute to CRC etiology. Several studies have suggested composition of the gut microbiota could impact human health, and gastrointestinal microbial dysbiosis has been observed in CRC patients ( Kamali Dolatabadi et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%